Islam dan Fundamentalisme Dalam Al-Quran - Melih, Ahmad Ghazali bin; Rahmah, Aulia; Ardiana, Syifa Salsabila; Rizal, Zamzam Khoirul (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
Fundamentalism is an ideology that adheres firmly to the basic principles of a particular religion, ideology, or belief. In Islam, fundamentalism is often associated with a literal interpretation of the Qur’an and Hadith, which can have implications for the rejection of modernization and social development. This study discusses the concept of fundamentalism from a historical, theological, and social perspective, and relates it to the concept of ghuluw in the Qur’an mentioned in QS. An-Nisa: 171 and QS. Al-Ma’idah: 77. This study also describes how fundamentalism in Islam has developed since the early days of the Khulafaur Rasyidin to the contemporary era, including its influence on political and social dynamics. The opinions of scholars indicate that ghuluw can appear in two main forms: extreme in glorification and extreme in rejection of certain teachings. Islam itself emphasizes balance in religion and the importance of understanding teachings holistically and contextually. Thus, this study highlights the need for a more critical approach in understanding the phenomenon of fundamentalism, by considering historical, social, and theological aspects to gain a more comprehensive perspective in seeing its impact on the development of Muslim society